1998
DOI: 10.1021/ic9715815
|View full text |Cite
|
Sign up to set email alerts
|

Tetranuclear Tetrapyrido[3,2-a:2‘,3‘-c:3‘‘,2‘‘-h:2‘‘‘,3‘‘‘-j]phenazineruthenium Complex:  Synthesis, Wide-Angle X-ray Scattering, and Photophysical Studies

Abstract: The tetranuclear ruthenium complex {Ru[(tpphz)Ru(bpy)(2)](3)}(8+), where tpphz is tetrapyrido[3,2-a:2',3'-c:3",2"-h:2"',3"'-j]phenazine, has been synthesized by reaction of [Ru(tpphz)(3)](2+) with [Ru(bpy)(2)Cl(2)] and by reaction of [Ru(bpy)(2)(tpphz)](2+) with [Ru(DMSO)(4)Cl(2)]. The large distance between the chiral centers allows full (1)H NMR interpretation despite the mixture of eight stereoisomers. The tetranuclear complex was further characterized by electrospray mass spectrometry and by the wide-angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 22 publications
7
33
1
Order By: Relevance
“…We should explicitly note that the dimers P and Q are not luminescent (for excitation wavelengths between 320 and 480 nm) both at room temperature in MeCN solution and at 77 K in a butyronitrile rigid matrix, which is contrary to what was found for the related tpphz and dppz complexes (Bolger et al 1996;Ishow et al 1998Ishow et al , 1999Campagna et al 1999;Chiorboli et al 1999;Flamigni et al 2000).…”
Section: Photophysical Properties Of P and Qcontrasting
confidence: 66%
See 1 more Smart Citation
“…We should explicitly note that the dimers P and Q are not luminescent (for excitation wavelengths between 320 and 480 nm) both at room temperature in MeCN solution and at 77 K in a butyronitrile rigid matrix, which is contrary to what was found for the related tpphz and dppz complexes (Bolger et al 1996;Ishow et al 1998Ishow et al , 1999Campagna et al 1999;Chiorboli et al 1999;Flamigni et al 2000).…”
Section: Photophysical Properties Of P and Qcontrasting
confidence: 66%
“…This corresponds well with p 0 (LUMO) and p 1 (LUMO+1) orbital descriptions in that the coordinating nitrogens on tatpp show little to no orbital density in p 0 but large orbital densities in p 1 , suggesting weak and strong coupling with the Ru dp (t 2g ) orbitals for p 0 and p 1 , respectively. We and others have previously used this localized description of the orbital properties/excited state electron localization as a useful way of interpreting the spectroscopic, photophysical and redox data for tatpp, tatpq, tpphz, and dppz complexes (Chambron et al 1985;Amouyal et al 1990;Fees et al 1993;Bolger et al 1996;Ishow et al 1998Ishow et al , 1999Campagna et al 1999;Chiorboli et al 1999;Flamigni et al 2000;Pourtois et al 2004). …”
Section: Assignment Of the Electronic Spectra Of P And Its Reduced Formsmentioning
confidence: 99%
“…Previous studies on tatpp dimers as well as dimers with shorter tetrapyridophenazine (tpphz) ligands have shown that the stereochemical isomerism is not detectable in simple linear dimers, as the stereocenters are anywhere from 12 A (in tpphz dimers) to 17 A (in tatpp dimers) and cannot approach any closer. [34][35][36][37][38] This is not exactly the case with the tetramer in which stereocenters on the same tatpp portion are still spatially separated, however, stereocenters on adjacent tatpp units can and do interact. This is most readily observed in the downfield doublets at 9.66, 9.70, and 9.74 ppm, which are present in a 2:4:2 ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Such ligands have attracted attention due to their use as connecting building blocks for supramolecular assemblies. If large-surface ligands feature more than one ligand donor site, connection between neighboring complexes can be realized through normal metal coordination (Ishow et al, 1998), but the large system also allows for strongstacking interactions. (Kammer et al, 2006;Gut et al, 2002).…”
Section: Chemical Contextmentioning
confidence: 99%